Legal Aspects of Election Administration Decisions Stages of Vote Counting Recapitulation in Pidie Jaya Regency - Zakaria, Muzakkir (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2024)
The 2024 general election in Indonesia is seen as procedurally successful in its implementation. However, if viewed substantially and in terms of fulfilling the aspect of justice, there are still many legal problems. The purpose of the study was to determine the legal aspects of the considerations of the correction decision by Bawaslu RI and the evidence process by Bawaslu Pidie Jaya in handling administrative violations of the recapitulation stage of the vote count of the election. This research is normative legal research, in its implementation it was carried out using a statute approach and a case approach and to strengthen secondary data, the reviewer added field data (field research) for primary data collection by conducting interviews. The results of the study showed the considerations and rulings of Bawaslu RI which stated that the reported party II was not involved and there were no facts stating that Reported Party II had committed an unlawful act according to the Pidie Jaya Regency Bawaslu Decision Number 001 / LP / ADM.PL / BWSL.KAB / 01.22 / III / 2024, according to the Reviewer, the considerations of Bawaslu RI in its decision No. 003/KS/ADM.PL/BWSL/00.00/111/2024 seen from the legal principle only emphasizes the principle of legal certainty alone and ignores the facts that occurred in the field during the recapitulation process of the vote count by ignoring the principle of legal benefit and the verdict of the Indonesian Election Supervisory Body which ordered the PPK to make improvements to the recapitulation of the vote count for DPRK candidates in Bandar Baru District based on C Results-DPRK caused legal problems and in its implementation caused problems. In the decision to handle administrative violations committed by the Pidie Jaya Regency Election Supervisory Body, the examination and evidence process has not been carried out effectively to find trial facts, so improvements are needed in the enforcement of election law in the future to provide justice and legal benefits.